1992
DOI: 10.1090/s0002-9939-1992-1100648-0
|View full text |Cite
|
Sign up to set email alerts
|

d’Alembert functional equations in distributions

Abstract: Abstract.In this paper we shall develop a method to define and solve the D'Alembert functional equation in distributions. We shall also show that for regular distributions (i.e., locally integrable functions) the distributional solution reduces to the classical one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…After the work of Hyers, the stability problems of various functional equations, such as Pexider equation [10], D'Alembert functional equation [7], Quadratic equation [3], and so on, have been investigated by a number of authors.…”
Section: Introductionmentioning
confidence: 99%
“…After the work of Hyers, the stability problems of various functional equations, such as Pexider equation [10], D'Alembert functional equation [7], Quadratic equation [3], and so on, have been investigated by a number of authors.…”
Section: Introductionmentioning
confidence: 99%
“…Many well-known functional equations have been studied in the Schwartz distributions (see [2], [3], [4], [5], [10] and [11] etc.). Actually it was shown that most of these functional equations in the distributions reduce to the classical ones.…”
Section: Introductionmentioning
confidence: 99%
“…When we reformulate the above equations in the Gevrey distributions we do not follow the method using operators in [2], [3], [4] and [10], [11], but use fundamental properties of generalized functions such as the tensor product and the pullback of Gevrey distributions. In fact, this method gives essentially the same formulation as in [2], [3], [4] and [10], [11], but the final form of each equation looks like the classical one.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations